Nomino-Adjectival Collocation in Written Production of L2 French - Kazlauskienė, Vitalija (Taikomoji kalbotyra, 2021)
The acquisition of lexical competence is complex, since it is not enough for learners to distinguish the form and the meaning of a lexical element in order to know how to correctly integrate it into the language context. Learners prefer some lexical combinations to others. Generally speaking, these combinations are determined by usage and by frequency of use in the target language. The question of frequency leads to characterizing the particular cases of co-occurrences as collocations (Anctil, Tremblay 2016). According to Tutin and Grossmann, “one often characterizes collocations by the fact that the meaning is transparent in reception (it is “guessed”), whereas, for a non-native speaker, it is difficult to produce the appropriate lexemes” (Tutin, Grossmann 2002). We will try to verify this statement and define the regularities of lexical combinations in L2 French interlanguage of Lithuanian learners. The aims of this presentation is to take stock of the frequencies and particularities of nomino-adjectival collocations in the written productions of non-native French learners, without claiming to be exhaustive. Thanks to the corpus at our disposal, we have extracted certain characteristics of nomino-adjectival collocations specific to interlanguage. Nomino-adjectival collocations are characterized by the structure (Adj) + N + (Adj) in the corpus. Collocations of the N + Adj type are more frequent than that of the Adj + N type. The corpus also reveals that the combination of words is not always characteristic of the general language. The process of interference and hybridization can be seen as an essential contamination of collocations, both lexically and syntactically. However, partially set phrases, in other words collocations, are an important way of expressing themselves for learner with B1 level. The results of this study demonstrate that the analysis of collocational constructions can reveal the relationship between competence and performance of speakers. This type of data could also form the basis of various scientific approaches relating to teaching and learning of foreign languages.
Keywords: collocation; co-occurrence; SN; corpus; L2